Freedom of Religion An Ambiguous Right in the Contemporary European Legal Order - Bernitz, Hedvig; Enkvist, Victoria (Swedish Studies in European Law, 2020)
This open access book presents a variety of perspectives on the concept of freedom of religion in different European countries against the background of the European Convention on Human Rights, the EU Charter of Fundamental Rights and other international treaties. In most European societies today, religion and questions about religion are increasing in relevance and importance. This development can be explained in several ways, for example by continuous demographic changes and new societal standards and values. As a consequence, the debate on the interpretation and scope of the right to freedom of religion has intensified in politics, media and, of course, law. The right to freedom of religion is complex and varies within different legal contexts at the international, European and national levels. This has resulted in a right that is ambiguous and sometimes difficult for individuals to claim and for states to assert. This book contains contributions from leading legal scholars working in these fields in Sweden, the Nordic countries and wider Europe. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the Swedish Studies Network.